Exploring Development Communication Strategies in Preventing Violent Extremism in Ghana: Case Study of the West Africa Centre for Counter Extremism (WACCE) - Ayanleke, Lawrence (UniMAC-GIJ, 2020)
Violent extremism (VE) fully gained attention of the UN in 2015 even though that was not the beginning of the canker in the world at least was the first time the issue was brought up for discussion to finding a collective solution to the challenge. It is a common knowledge that issues of VE has been with the world since time in memorial but it is interesting to note that VE takes different shapes in different parts of the world depending on the drivers. Violent extremism is an issue of concern to almost every country in the world today and those in Africa are not exception. There are several push and pull factors that promote VE, hence there is no simple solution to preventing VE. Unfortunately, developing countries like Ghana are those that are most negatively affected on socio, economic and cultural grounds. Ghana is yet to witness a full-fledged VE activities recorded in the country but they were pockets of violence that fit into the typology of VE in Ghana. The consequences and destructive nature of VE among other things is a major challenge to peace in most developing countries in the world today. VE has an unfortunate reputation and potential to impede the attainment of Sustainable Development Goals (SDGs) in low-income countries. In the face of the threat posed by VE, as a matter of great concern the United Nations came up with a “Master Plan” in 2016 to prevent the canker with a consented global effort and to attract the world’s attention to the phenomenon. The UN General Secretary’s Plan of Action to Prevent Violent Extremism provided impetus for Member States to draft and domesticate Regional and National Plan of Action to Prevent Violent Extremism (PVE) to meet regional and national realities. The Plan of Action requires whole-society approach centred on human security and the community should be at the core of preventing VE. Communication has long been identified as one of the effective tools in PVE. Interesting, four out of the seven key area actions recommended for PVE namely Dialogue, Community Engagement, Empowerment, the Internet and Social Media are all core Development Communication Strategies that envisage a two-way communication approach that is pragmatic, value-laden and human-centric. The objective of this research is to explore the four key area actions recommended by the UN (or Development Communication Strategies) and how effectively Civil Society Organizations (CSOs), Prevention and Countering Violent Extremism (P/CVE) Practitioners are deploying these measures in preventing and countering VE. This research also aims at investigating results of the measures as suggested by the UN. The West Africa Centre for Counter Extremism (WACCE) is used as a case-study to have an in-depth understanding of the typology of VE in Ghana and the measures used in preventing and countering the scourge
Thesis